Information and Communication Technology: A Drive for Entrepreneurial Education for Sustainable National Development - Chiroma, Aminu Ahmed; Abifarin, Michael Segun (NIU Journal of Social Sciences, 2018)
The study looks at the possible entrepreneurial opportunities inherent in information and communication technology. The paper briefly defines the concept of information and communication technology and entrepreneurial education as given by some authors. The study explains the various ICT entrepreneurial possibilities which young Nigerians and other people can venture into become job creators. For instance, people can engage in data management services, networking, computer hardware and software engineering, data base and soft ware design, management and administration of ICT, computer repairs, handset repair and other related entrepreneurial ICT possibilities. It also identifies some constraints to entrepreneurial education in ICT which include lack of funds for establishment and maintenance of ICT facilities and services, problem of constant power failure, lack of entrepreneurial mindset of the people, lack of sufficient ICT experts to run the programme and problem of constant technology change which quickly make some ICT equipment to be outdated. The study concludes by urging government, private sectors and organizations to encourage people to exploit the entrepreneurial opportunities in ICT. Keywords: Information Communication technology-drive, entrepreneurial, education, sustainable, national development.